Proximity strategies in outsourcing relations: The role of geographical, cultural and relational proximity in the European automotive industry - Schmitt, Alexander; Van Biesebroeck, Johannes (Journal of International Business Studies, 2013)
Several trends that affect the manufacturing of sophisticated goods – increasing international fragmentation of production, and lean and modular process technologies – have increased the importance of proximity in the supply chain. We use the case of the European automotive industry to simultaneously evaluate the relative importance of three dimensions: geographical, cultural, and relational proximity. Using a rich and novel data set, we find that carmakers value some aspects of each dimension independently in their sourcing strategy. The estimates indicate which proximity measures provide the largest (independent) benefits, but also that the positive effects the literature has attributed to some measures tend to reflect past relationships rather than predict new ones. In particular, co-location and a low cultural distance should be interpreted as outcomes of a sourcing strategy, not as predictors for sourcing success. Finally, we investigate to what extent firms from different countries follow different strategies, and which choices suppliers can make to boost their attractiveness as outsourcing partners.